Towards National Methodologies for Measuring Corruption Perceptions - Hohmann, Balázs (Közigazgatási és Infokommunikációs Jogi PhD Tanulmányok, 2025)
The aim of this paper is to examine internationally used methods for measuring corruption perceptions and to draw findings and conclusions on the need for national corruption perception methodologies and how they can be aligned with international approaches. The article's findings suggest that there are a number of technical criticisms of international indicators regarding their validity, reliability and objectivity, which could be addressed by the development of a national indicator, while potentially improving aspects of the international indicator with respect to the above issues. The findings of this article are based on the results of the research and preparatory study carried out by the author in the framework of the KÖFOP-2.2.3-VEKOP-16-2016-00001 project, so-called "Capacity building and awareness raising for the increased detection and prevention of corruption cases".